Denunciation and Social Control - Bergemann, Patrick (American sociological review, 2017)
It has long been observed that centralized social control requires some level of cooperation from the populace. Without such assistance, control agents are unable to acquire the local knowledge necessary to locate and prosecute deviants. Yet why citizens cooperate with authorities, especially in the most repressive regimes, remains a puzzle. This article develops two models of such cooperation: in the first, authorities actively use incentives to elicit denunciations from the populace, through either coercion or the promise of rewards. In the second, authorities passively gain access to local negative networks, as individuals denounce to harm others whom they dislike and to gain relative to them. Using internal variation in the early years of the Spanish Inquisition (1486 to 1502) and Romanov Russia (1613 to 1649), I demonstrate the differing effects of each model on patterns of denunciations. Paradoxically, social control is most effective when authorities provide individuals maximum freedom to direct its coercive power.